Violent Thefts Involving Teenagers And Women (Criminology in Sociological Perspective) - Ari Wijaya, Oscarius Yudhi; Muriman, Chairul - (Faculty of Law, Universitas Pekalongan, 2024)
The goal of this research was to find a scientific explanation for the issue of women and teenagers being involved in violent theft crimes that have already started, as well as to find and construct theoretical justification based on current theories, including sources from books and research journals. This study employed a qualitative research design in conjunction with a literature review. According to the findings of research, women are viewed as potential home educators of their children and should be given recognition and equality, while teenagers are viewed as the country's future generation, potential leaders, and catalysts for community and national development. rather than feeling scared by his family or other societal members, he feels adequate in the social system of society. He thus isolates himself by creating an exclusive group, which prompts him to take illegal and/or violent acts, such as muggings and thefts, in violation of both community standards and the law.